2012
DOI: 10.1007/s10570-012-9668-6
|View full text |Cite
|
Sign up to set email alerts
|

Blending cellulose with polyethylene-co-acrylic acid in alkaline water suspension

Abstract: Alkaline solutions of cellulose and polyethylene-co-acrylic acid (PE-co-AA) were mixed in order to prepare homogeneous cellulose/PE-co-AA blends. Different mixing methods were tested and the evolution of solutions was characterized by rheological methods and optical microscopy. In addition to the solution stage studies, the precipitated dry blends were characterized by Differential Scanning Calorimetry, Scanning Electron Microscopy, Fourier Transform Infrared and Dynamic Mechanical Analysis. Mixing the solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…Figure (b,c) T C = 69°C]. This same phenomenon was observed in the earlier studies (Saarikoski et al and Lipponen et al) which clearly indicated that the polymers were mixed. Rigid/solid cellulose was able to act as a strong nucleation agent for the molten PE ‐co‐ AA phase during the cooling.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Figure (b,c) T C = 69°C]. This same phenomenon was observed in the earlier studies (Saarikoski et al and Lipponen et al) which clearly indicated that the polymers were mixed. Rigid/solid cellulose was able to act as a strong nucleation agent for the molten PE ‐co‐ AA phase during the cooling.…”
Section: Resultssupporting
confidence: 86%
“…This freeze–melting method between the mixing steps was done in order to dissolve any cellulose which may have gelled during mixing. The effect of this procedure is explained in more detail in an article by Saarikoski et al The blending process is presented in Figure . The polymer compositions of the blend dispersions are represented in Table .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The EAA polymer was selected mainly due to it being insoluble in water and having the ability to form a stable aqueous dispersion. Also, this modified polyethylene had previously shown good adhesion and compatibility with regenerated cellulose (Saarikoski et al 2012). Composites with up to 70 vol% dry content CNF could be made.…”
Section: Introductionmentioning
confidence: 94%